Long-term migration and remittances in the Alpine district of Gornji Grad: human agency amid environmental and social constraints - Sedlaček, Janja (Dve domovini, 2025)
This article examines emigration from the Alpine district of Gornji Grad between the late 19th century and the early 20th century, focusing on the interplay between environmental constraints and human agency. It analyzes how hereditary and marriage customs, timber cutting and rafting, and migration functioned as adaptive responses to environmental limitations and as agents for economic diversification. The study also explores the reciprocal effects of migration through financial and social remittances.
Keywords: alpine communities; alpske skupnosti; denarni in socialni transferji; financial and social remittances; history; integrated peasant economy; integrirana kmečka ekonomija; migracije; migration; zgodovina